Kegiatan Sosial Mengajar Mengaji Iqra dan Al-Qur’an di TPA Al Fajar, Dusun Teluk Lihat - Elfianto, Isa (Yayasan Daarul Huda Kruengmane, 2024)
The Al-Qur'an Education Park (TPA) is one of the educational institutions in the field of religion that is often found in the community. TPA Al Fajar is proof of the existence of an Islamic religious educational institution that reaches the hamlet level. TPA Al Fajar is located in Teluk Lihat Hamlet, Lemo I Village, Teweh Tengah District, North Barito Regency, Central Kalimantan Province. TPA Al Fajar had faced a vacuum due to several factors. Therefore, DKM PAMA SMM conducted a Social Activity of Teaching the Iqra and Al-Qur'an as an effort to reactivate the teaching and learning activities of TPA Al Fajar. The purpose of this activity is to introduce the hijaiyah script and direct Muslim children in Teluk Lihat Hamlet towards the Qur'ani generation. Technically, this social activity contains 3 stages of implementation, including: the preparation stage, the implementation stage, and the evaluation stage. This social activity uses two learning styles as methods, namely auditory with lecture techniques and visual with reading practice techniques. Social Activities Teaching the Iqra and Al-Qur'an to Recite the Quran is a solution to problems in the field through the reactivation of the TPA Al Fajar teaching and learning activities.